A Psycho-Spiritual Transformation in COVID-19 Crisis Narratives: A Comparative Study in Indonesia and Pakistan - Prakosa, Heru; Widyarini, Nurlaela; Utama, Johanes Seno Aditya; Carlos, Juan (UI Scholars Hub, 2026)
Although the COVID-19 pandemic ended as a global health emergency, its psychosocial legacy persists in many communities. This study examines how religion and spirituality support recovery in Indonesia and Pakistan by shaping crisis narratives. Faith-based language is treated as psychosocial data and interpreted through its functions in meaning-making, emotion regulation, social connection, value anchoring, and action commitment using Psycho-Spiritual Transformation (PST) as a guiding framework. Open-ended responses were collected from 274 participants via an online survey in July 2021 (Indonesia n = 236; Pakistan n = 38). Across both contexts, narratives typically moved from pressure and inner conflict toward spiritual and relational reassurance and then toward renewed ethical orientation and practical commitments, including prosocial intentions and health-protective behaviors. The overall pattern was broadly similar across these two countries, indicating a shared faith-based meaning reconstruction grammar in highly religious societies. However, the Indonesian narratives more often combined diverse coping elements and translated faith into practical commitments, whereas the Pakistani narratives more strongly emphasized spiritual and relational reassurance. The findings highlight PST as a useful lens for distinguishing supportive faith discourse from forms of resignation that may hinder adaptive coping.